Insight into Potential Biomedical Application of Mesoporous Materials - Irene Alexandra Spiridon; Irina Draga Căruntu; Iuliana Spiridon; Radu Brăescu (MDPI AG, 2022)
The physicochemical properties of many drugs have a decisive impact on their bioavailability, as well as the pharmacokinetic efficiency in various disease therapeutics. That is why mesoporous materials have attracted a special interest in the drug delivery field, facilitating the loading of drugs into their pores due to their high surface area and porosity. The interfacial interactions established with drug molecules represent the driving force for efficient drug loading and controlled release kinetics. Moreover, these materials offer an optimal design for implantable local-delivery devices or for improving the accuracy of imaging techniques in clinical diagnosis. Their use is validated by improvements in therapeutic outcome and prevention of side effects. This review discusses the role of mesoporous materials in different biomedical applications.